Podnikatelský záměr - založení podnikání v oblasti topenářství a instalatérství - Sklenářová, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Cílem bakalářské práce je vytvořit podnikatelský záměř v oblasti instalatérství a topenářství. Práce je rozdělena ne teoretickou část, analýzu současné situace a vlastní návrhy řešení. V teoretické části je popsáná teorie spojená s tvorbou podnikatelského plánu, na jejímž základě je podnikatelský plán vypracován. Hlavním cílem práce je zjistit, zda bude návrh plánu realizovatelný.

The aim of this bachelor thesis is to create business plan in the plumbing and heating field. The bachelor thesis is divided into the theoretical part, the analysis of current situation and suggestion of solution. There is decribed the theory relating to the creating a business plan in the theoretical part. This theory is basis for making the business plan. The main aim of the thesis is to figure out if the suggestion can be realized.
Business Plan - Establishing a Business in The Field of Heating and Plumbing
Keywords: Podnikatelský záměr; podnikatel; podnikání; Business plan; entrepreneur; business